Towards a definition of neurodisability: a Delphi survey. (5th August 2013) - Morris, Christopher; Janssens, Astrid; Tomlinson, Richard; Williams, Jane; Logan, Stuart
<x xml:space="preserve">Abstract</x> Aim The aim of this study was to develop, systematically, a consensus‐based definition for 'neurodisability' that is meaningful to health professionals and parents of children with neurological conditions. Method A multidisciplinary group of health professionals was recruited through child development teams and professional societies in the UK; several parents of children with neurological conditions worked with the research team. Professionals participated in three rounds of a Delphi survey. Participants rated their agreement with a proposed definition in each round, and feedback was used to refine the definition. Finally, a perspective was sought from international experts. Results Responses to the three rounds were as follows: round 1, 245 out of 290 (84.4%); round 2, 242 out of 300 (80.6%); and round 3, 237 out of 297 (79.7%). Agreement with the proposed definition was extremely high in every round (89.0%, 90.1%, and 93.6% respectively). The final version of the definition was widely endorsed among professionals, parents, and a small number of international colleagues. The final definition is as follows: 'Neurodisability describes a group of congenital or acquired long‐term conditions that are attributed to impairment of the brain and/or neuromuscular system and create functional limitations. A specific diagnosis may not be identified. Conditions may vary over time, occur alone or in combination, and include a broad range of severity and complexity. The impact may include difficulties with movement, cognition, hearing and vision, communication, emotion, and behaviour'. Interpretation An agreed definition of neurodisability will be useful for conducting research or clinical evaluations with people affected by neurological problems.